Muscle-to-bone and soft tissue-to-bone ratios in track and field athletes - Westerberg, Hannah; Stanforth, Philip R.; Carbuhn, Aaron; Bosch, Tyler; Dengel, Donald R (International Journal of Sports Medicine, 2025)
The purpose of this study was to compare the muscle-to-bone (MBR) and soft tissue-to-bone ratios (SBR) of 459 track and field athletes across event groups to identify differences in MBR and SBR. Dual X-ray absorptiometry provided total and regional (i.e., arm, leg, trunk) lean mass (LM), fat mass (FM), and bone mineral content (BMC). MBR was calculated by dividing LM by BMC. The SBR was calculated by dividing LM+FM by BMC. Kruskal-Wallis tests were used to compare ratios across event groups. Dunn’s post-hoc tests were utilized to adjust for multiple comparisons. Total MBR for females was higher in the throwers compared to the multievent athletes (p=0.02). For the males, total MBR was lower in jumpers compared to all events except pole vaulters (PV) (p<0.05). Trunk MBR was higher in the long-distance runners (LD) compared to jumpers, PV, and throwers (p<0.05). The throwers had higher total, arm, and leg SBRs compared to the jumpers, LD, middle distance, PV, and sprint groups (p<0.05). Significant differences in total and regional MBR and SBR were identified across event groups for both sexes, and may indicate event-specific adaptations impacting the balance between soft tissue and bone.
Keywords: bone health; body composition; athletics; injury risk